2019
DOI: 10.1108/imefm-04-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Co-movements and diversification opportunities among Dow Jones Islamic indexes

Abstract: Purpose This paper aims to analyse the opportunity of an exclusive investment in the DJ Islamic indexes. The objective is to characterize the links between MENA region index with seven DJ Islamic indexes. Design/methodology/approach A co-movement analysis was conducted to assess whether there is a safe investment during crisis. The VECM verifies the existence of a long run association. The MGARCH-DCC characterizes the dynamic links. The wavelet coherence detects a correlation in a time-frequency domain, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The literature also sheds some light on whether investing in Islamic equity funds can provide additional diversification benefits to conventional portfolios. Again, overall, the findings do not represent a consensus on this topic: some studies support the notion that investing in Islamic equity funds serves as an effective risk diversification strategy vis-à-vis investments in mainstream equity funds (Antar and Alahouel, 2019; Balcılar et al , 2015; Saiti et al ,2014). In other studies, researchers found that Islamic and conventional equity funds are strongly correlated (El Alaoui et al , 2015; Hammoudeh et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 73%
“…The literature also sheds some light on whether investing in Islamic equity funds can provide additional diversification benefits to conventional portfolios. Again, overall, the findings do not represent a consensus on this topic: some studies support the notion that investing in Islamic equity funds serves as an effective risk diversification strategy vis-à-vis investments in mainstream equity funds (Antar and Alahouel, 2019; Balcılar et al , 2015; Saiti et al ,2014). In other studies, researchers found that Islamic and conventional equity funds are strongly correlated (El Alaoui et al , 2015; Hammoudeh et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 73%
“…Due to the small and illiquid stock market and difficulties in generating foreign trading volumes, many countries create linkages with other Islamic exchange markets (Hassan & Yu, 2007). According to Antar and Alahouel (2020), there are some regional differences in stock market performance; thus, MENA investment portfolio managers should not invest in indices in Europe, the United Kingdom or emerging markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The measurement and selection of financial products should be consistent with Shariah criteria to avoid a conflict with the essence of Islam, which might create an obstacle in the development and growth of Islamic finance (Antar & Alahouel, 2020; Hakim & Rashidian, 2000). Financial products are evaluated through the Shariah Supervisory Board in accordance with Islamic Shariah, and products that do not conform to Shariah principles are excluded (Mansor & Bhatti, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To explain how diversification diminishes risk, supposing the covariance is less than one (invariable true) will lead to a standard deviation less than the weighted average of the standard deviation of the expected returns of the securities. There have been numerous research studies conducted subsequent to these studies, which empirically test the covariance of asset returns amongst the stock market to explain portfolio diversification opportunities (Antar and Alahouel, 2020;Buriev et al, 2018;Saiti et al, 2014Saiti et al, , 2020. If there is a high correlation amongst the asset returns, it will decrease the whip hand of diversified investment portfolios (Xiao and Dhesi, 2010).…”
Section: Theoretical Underpinnings 21 International Portfolio Diversificationsmentioning
confidence: 99%